Rigid swelling of sublingual caruncle area due to the salivary gland duct obstruction by a sialolith - Fred Bernardes Filho; Gustavo Martins; Andreia Oliveira Alves; José Ronaldo Vieira da Costa; David Rubem Azulay; Luna Azulay-Abulafia (Sociedade Brasileira de Dermatologia, 2014)
Sialolithiasis is the presence of calculus within the ductal system of a salivary gland. Among the diagnostic methods are inspection, palpation, checking the amount of saliva secreted and the identification of a sialolith. The authors present the case of a 37-year-old female patient with edema of the submandibular area and a bulging sublingual caruncle due to a calculus that obstructed the salivary gland ostium.